Thermo‐physical properties of nonlinear optical crystal K3B6O10Br. Issue 2 (18th March 2016) - Xia, Mingjun; Xu, Bo; Liu, Lijuan; Wang, Xiaoyang; Li, Rukang; Chen, Chuangtian
Abstract : The thermo‐physical properties of K3 B6 O10 Br crystals along the principal directions were systematically investigated. These properties are of importance for its practical application at high average power laser output. Abstract : The thermo‐physical properties of the nonlinear optical (NLO) crystal K3 B6 O10 Br (KBB) were experimentally investigated, including specific heat, thermal conductivity, coefficient of thermal expansion and refractive index. The specific heat of KBB is lower than that of LiB3 O5 and higher than that of other borate NLO crystals, such as β‐BaB2 O4, CsLiB6 O10 and CsB3 O5, and KBB manifests a high damage threshold because of its lower temperature gradient during laser pulse irradiation. The thermal expansion coefficients were obtained as α x = 5.09 × 10 −6  K −1 and α z = 2.39 × 10 −5  K −1, showing weaker anisotropy than those of commonly used NLO crystals. The temperature‐dependent Sellmeier dispersion equations of the refractive indices were also obtained, and the phase‐matching angles for second harmonic generation (SHG) at temperatures of 313, 343, 373, 403 and 433 K which were calculated from these equations are in good agreement with the experimental values. All results are indicative of the KBB crystal as a novel promising NLO crystal for high power SHG.